In search of sharia-compliant resolution framework for Islamic banks: The case of Indonesia - Rulindo, Ronald; Rifqi, Muhammad (Jurnal Ekonomi & Keuangan Islam, 2022)
Purpose – This paper investigates Sharia concerns on existing bank resolution framework and propose recommendations on how to resolve those concerns in Sharia-compliant manners. It also assesses compatibility of resolution powers mandated by the FSB’s Key Attributes of Effective Resolution Regimes for Financial Institutions if applied to resolve failed Islamic bank, especially focusing on operational aspect of executing the resolution options. Methodology – We conduct a series of focus group discussion with various relevant stakeholders, including Indonesian Sharia scholars, regulators, professional associations, Islamic bankers and academics. The discussions were performed in group interviews format, with the authors took part as moderators. The discussions took place between July 2020 to January 2021, and were part of development of fatwa and regulations on the resolution for Islamic banks. Findings – In general, the existing bank resolution framework can be applied to Islamic banks. However, there are some resolution powers of the authority that possesses inherent sharia issues, but are still allowed according to Dewan Syariah Nasional (DSN) (the National Sharia Council). There should be clear measures attached to those powers prior to implementation. For some aspects, some adjustments to the resolution powers are also needed through establishment of infrastructures and regulations, particularly with regards to resolution options. Originality – The novelty of this study is the analysis of suitability of banking resolution issues from Sharia perspective. This paper also serves to enhance awareness on issues related to resolution of Islamic banks and promote wider implementation of Sharia approaches for bank resolution in other jurisdictions.